Securing Access using Proxy Integrated with Antivirus - Mohd Nor, Nur Izyan Nabihah (Journal of Computing Technologies and Creative Content, 2019)
These days, web surfing is important in our daily life. We used search engine such as google, msn or yahoo to search something. Most of students of University Kuala Lumpur Malaysian Institute Information Technology (Unikl MIIT) will browse to the internet to search document or any references that related to their assignment, but not all of them browse to the secure URL or web page. This project aimed to manage blacklist and block any URL from student to access using squid proxy integrated with clam antivirus. Other than manage and block any website to access, this project also aimed to improve the squid proxy log by using Web GUI instead of view from the common log file format. It will ease the administrator to manage and analyse the log file. The embedded server is used as a main hardware platform to install Centos 7 Operating System. To configure and integrate with antivirus, the developer used squid proxy as a server and used clamAV database as the antivirus. The testing is implemented using the several lists of websites and also downloaded the virus file. It shows the system worked well as it blocked the website from being access. The administrator also can manage and view the user’s activities from the squid access log dashboard.